(untitled) (NAU Journal of Library and Information Science, 2025)
The objective of the study was to examine the impact of Information Communication Technology on the acquisition of library materials in Federal Polytechnic, Oko. Specifically, the study identified the impact of ICT on the acquisition of library materials and the challenges of employing ICT in the acquisition of library materials. The study was guided by three research questions. A descriptive survey research method was used to elicit responses from the entire population of 30 library staff of Federal Polytechnic Oko Library. The instrument for data collection was a questionnaire. The data were analyzed using descriptive statistics (mean scores and frequencies). The findings revealed that cost savings as a result of using ICT for material acquisition; positive impact of ICT on the acquisition of library materials and improved efficiency of library material acquisition are the impact of ICT on the acquisition of library materials. The challenges identified were budget constraints and lack of staff training. The recommendations of this study include: the training of staff on ICT applications, the upgrade of ICT infrastructure, and addressing the challenges facing ICT implementation, like budget constraints and technical issues among others. ICT has greatly impacted the acquisition of library materials, and its effect can be seen in the increased efficiency of library acquisition, real-time inventory management, and speed or fastness in acquisition procedures, which should consistently be maintained by management. This study represents a fresh empirical investigation into the impact of Information Communication Technology on the acquisition of library materials in the Federal Polytechnic Oko library.